2007
DOI: 10.1007/s00228-007-0369-2
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to HAART therapy measured by electronic monitoring in newly diagnosed HIV patients in Botswana

Abstract: Aims This pilot study was designed to evaluate the feasibility and benefits of electronic adherence monitoring of antiretroviral medications in HIV patients who recently started Highly Active Anti Retroviral Therapy (HAART) in Francistown, Botswana and to compare this with self-reporting. Methods Dosing histories were compiled electronically using Micro Electro Mechanical Systems (MEMS) monitors to evaluate adherence to prescribed therapies. Thirty patients enrolled in the antiretroviral treatment program were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 24 publications
2
28
0
1
Order By: Relevance
“…However, the difference between electronically monitored and self-reported adherence was not surprising, and was similar to those described in prior studies of adherence. 40,74 It was nonetheless unexpected that only one measure of neuropsychological functioning was a significant predictor of adherence in the present study. Previous studies 22,24,41 have found that overall assessments of neuropsychological functioning, as well as measures of executive functioning and working memory, were significant predictors of adherence.…”
Section: Discussionmentioning
confidence: 52%
“…However, the difference between electronically monitored and self-reported adherence was not surprising, and was similar to those described in prior studies of adherence. 40,74 It was nonetheless unexpected that only one measure of neuropsychological functioning was a significant predictor of adherence in the present study. Previous studies 22,24,41 have found that overall assessments of neuropsychological functioning, as well as measures of executive functioning and working memory, were significant predictors of adherence.…”
Section: Discussionmentioning
confidence: 52%
“…Several recent studies have reported average adherence rates to ART up to 80% to 90% of prescribed doses (Etard et al, 2007;Vriesendorp et al, 2007;Williams, Clarke, Williams, & Barton, 2007) as compared with the average of 50% to other chronic medication (Altice & Friedland, 1998;Stone, 2001). The current study reported that pill count was the most commonly used method to measure treatment adherence.…”
Section: Challenges In Treatment Follow-upmentioning
confidence: 59%
“…One limit [20] to the electronic monitoring method is thought to be the effect of patient knowledge of being monitored, the 'Hawthorne effect' [21]. By contrast, some clinical studies have found poor adherence despite patients being aware of the monitoring.…”
Section: Discussionmentioning
confidence: 95%